(untitled) (Swiss Medical Weekly, 2012)
OBJECTIVE: To assess and compare clinical observations and interpretations by physicians trained in biopsychosocial internal medicine (group A) and a control group (C) of physicians with no such special training. METHODS: A verbatim first-interview of a 36-year old woman, seen for consultation by RHA, was presented to both groups (A, trained physicians: n = 30, and C, controls: n = 29). The patient’s symptoms included: shaky knees, strange sensations in the abdomen and chest, insecurity and dizziness. The symptoms had begun before her final nursing- exam and exacerbated on her mother’s 60th birthday two months later. The patient’s mother is the sole caretaker for the patient’s sister, who also attended the birthday party. The patient’s sister is 19 and had been diagnosed with storage disease and is wheelchair-bound. The doctors were asked to record their observations and interpretations while reviewing the case report. RESULTS: Group A-physicians mentioned and interpreted the physician-patient relationship and the patient’s body language as described in the case report more often (p = 0.002, Wilcoxon-Mann-Whitney rank sum test (RS)), mentioned physical symptoms more often (p = 0.0099, Fisher’s exact test (FE)) and more often interpreted illness settings with respect to the patient’s fear and guilt (Fisher’s exact test, p = 0.007 and p = 0.015). A precise integrative diagnosis (life events leading to stress, the latter evoking fear and guilt, leading to symptoms of the fight-flight reaction) was suggested by 7 of group A and 4 of group C. Extensive laboratory work-up and requests for consultations were more frequently asked for by the C group (p = 0.048, RS). CONCLUSION: Residency training in biopsychosocial medicine in an Internal Medicine Department increased sensitivity to and interpretation of biological and psychosocial data many years after the training and decreased the extent of work-up and consultation costs. However it only tended to enhance psychosomatic conceptualisation with respect to anxiety/guilt/hyperventilation and conversion symptoms.